PREVALENCE OF AMPUTATIONS IN DIABETIC INDIVIDUALS TREATED AT A REFERRAL CENTER (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Diabetes Mellitus (DM) has high rates of morbidity and mortality due to its complications. Objective: To analyze the prevalence of amputations in individuals with DM treated at a referral center in Salvador, Bahia. Method: Cross-sectional study, with data from 160 medical records adult people with diabetes who suffered or not amputation, attended at the specialized outpatient service. Data analysis was performed using the Statistical Package for the Social Sciences®. The results are presented in absolute and relative frequencies, χ2 test and Fisher’s exact test, when appropriate, considering significance of 5%. Results: The prevalence of amputation was 53.75%. It was associated with male gender (p=0;00), time since diagnosis of DM greater than 10 years (p=0.046) and metabolic comorbidities (p=0.047). Conclusion: The high rates of amputations in males of productive and working age reveal the need to control DM and its comorbidities, as well as prevention of skin lesions that lead to amputation.